FAKTOR YANG MEMPENGARUI KEBERHASILAN PESERTA DIDIK DALAM PEMBELAJARAN BAHASA INGGRIS (Teori Linguistik dan Al-Qur`an) - Andi Muhammad Dakhalan (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
The emergence of today`s role of English as an international language (EIL) and as a global lingua franca (ELF) makes English language education important in many countries. In Indonesia, for example, it has been growing a number of schools ranging from kindergarten to university level which use English as the medium of instructions.Every subject in school curriculum has different objectives including English subject. But some students donot realize that, learning English is really important in their life. It makes them unmotivated in learning English. Lack of learners` motivation is believed as one of the primary problems of English language teaching, many of them take it as a difficult lesson to learn. As a result, they skip class, and when they attend the class, it is not because they want to learn English but likely because they fear of failure. Moreover, lots of them may lack of attention during class, chatting with classmates, doodling in their note books or gasp in their textbooks. This present study aims at discovering the factors that influence the students` achievement in English language learning by using linguistic and Al-Qur`an theory. The conclusion of the study is the factors that influence the students` achievement in English language learning are the students` intelligence, motivation, school facilities, policies of government and the principal, family, and environment